TAXPAYERS’ PERCEPTIONS TOWARDS E-FILING SYSTEM APPLICATION: A DECOMPOSED THEORY OF PLANNED BEHAVIOR (DTPB) APPROACH - Hanum, Latifah (Profit: Jurnal Adminsitrasi Bisnis, 2019)
This research aimed to examine the perceptions of taxpayers in applying the Annual Tax Return e-Filing system with the approach of Decomposed Theory of Planned Behavior (DTPB) model by Taylor and Todd (1995).  This research is the development of the model used by Lee (2009), Azmi and Bee (2010), and Rana et al. (2015). The data of this research were collected using a survey method. The sample of this research was individual taxpayers in Malang City (Indonesia) who have been using the Annual Tax Return (SPT) e-Filing system. A total of 83 data were analyzed using SPSS version 23.0. The results showed that the taxpayers’ perceived usefulness, perceived benefit, and perceived behavioral control had an effect on behavioral interest or intention to use the e-Filing system. Meanwhile, the taxpayers’ perceived ease of use and perceived risk had no effect on the behavioral interest or intention to use the e-Filing system. It indicates that most taxpayers in Malang City have felt comfortable and accepted the presence of new technology in the world of taxation, especially in the reporting of Annual Tax Return. The tendency of taxpayers in Malang City to use the e-Filing system is not based on the perceived ease of use of the facility but rather due to the usefulness and need for such a facility in reporting tax return online, so taxpayers perceive that the e-Filing system does not  or will not pose a risk in its use.